HUBUNGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN TRUSTWORTHINESS DENGAN KINERJA ANGGOTA RESIMEN MAHASISWA - Purnama, Nicky Wahyu (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Performance is an important factor in an organization or company, because the state can be determined through performance and skill regularly and encourage the achievement of a healthy mutual relationship between superiors and subordinates. In the regiment, members can be said to have a good performance during an assignment if no violation of the rules, so it gets a good judgment of his superiors. In the execution of the entire ordinance will be associated with the performance of the members of the regiment. To realize a good performance and OCB members must have Trustworthiness. This study aims to determine the relationship between OCB and performance of members of the regiment Trustwhorthiness University of Surabaya. Researchers took the subject of study by 25 members of the regiment Univeritas Surabaya. Performance data collection variable, OCB, and Trustworthiness was obtained through a questionnaire. Based on the results obtained, Value koefisian correlation with the performance of OCB has a significance <0.05 is 0.001 and r value of 0.602. The results stated that there is a positive relationship between OCB performance. Trustworthiness of the performance has significance> 0.05 is 0.827 and r value of 0.034 so that there is no positive relationship between Trustworthiness with performance.